Optimalisasi Mutu Pendidikan melalui Manajemen Strategis Berbasis Analisis SWOT - Sizka Farwati (JMiE (Journal of Management in Education), 2025)
One of the main challenges in contemporary education lies in the ability of educational institutions to respond to rapid changes while continuously improving educational quality. Therefore, educational institutions are required to possess analytical capabilities to identify strengths, weaknesses, opportunities, and threats as a basis for formulating effective strategies. This study aims to describe the inhibiting and supporting factors of educational quality improvement, explain the importance of strategic management in enhancing educational quality, and analyze the role of SWOT analysis within educational strategic management. This research employs a literature review approach by examining relevant scholarly sources. The findings indicate that the inhibiting factors of educational quality improvement include policy inconsistency, centralized educational governance, and limited community participation. Meanwhile, supporting factors consist of school-based quality management, community involvement in education, and the development of effective learning paradigms. Furthermore, strategic management enables educational institutions to design adaptive and anticipatory strategies to ensure sustainable quality improvement. SWOT analysis serves as a strategic instrument that optimizes internal strengths, minimizes weaknesses, capitalizes on opportunities, and mitigates threats, thereby contributing significantly to the enhancement of educational quality.